Remaja Menjadi Homoseksual di Keluarahan Mangga Kecamatan Medan Tuntungan Kota Medan - Rizky, Syahira; Rangkuty, Rakhmadsyah Putra (FISIP Universitas Malikussaleh, 2024)
This research examines the process of teenagers becoming homosexual which is influenced by the social environment in Mangga sub-district, Medan Tuntungan sub-district, Medan city. This research focuses on the process of teenagers becoming homosexual and society's attitudes towards homosexual behavior. The theory used to discuss this research uses the social control theory of Travis Hirschi. The research method used is a qualitative research method with a phenomenological approach. The data obtained comes from data from observations, interviews and documentation. The results of the research obtained were that homosexual behavior in teenagers was motivated by a lack of love from the family, friendship environment, and lack of self-control. The process of teenagers becoming gay is based on individual experience starting from the emergence of feelings of admiration for members of the same sex, continuing with changes in lifestyle that resembles women's, as well as feeling comfortable with homosexual couples. Other results from this research also reveal that there is a dualism in society's attitudes towards the behavior of gay teenagers, namely attitudes of rejection and acceptance. Rejection is carried out in the form of scolding and advising, as well as not responding to this behavior. The form of acceptance by society, especially family and friends, is not to be hostile and stay away from it, for fear that it will further lead to deviant sexual acts.